Craft beer sector collaboration in North East Scotland: The role of individual success. (November 2020) - Cunningham, James; Barclay, Stephanie
Our understanding of craft brewing is beginning to grow and a key theme to emerge from this artistic and intrinsically creative sector is the dependence on collaboration between entrepreneurial agents. In the North East of Scotland, the growth in craft beer is also recognised to come from a deep rooted collaboration, as a reaction to and in resistance of large mainstream competition. However, one such enterprise, BrewDog, has grown to achieve global reach to rival that of the large-scale brewers the craft scene sought to challenge. We consider what this unprecedented success means for the remaining collaborators in the local craft beer sector. Our findings point to a shared optimism and possibility of achievement among the craft brewers, aided by BrewDog's success. However, the nature of collaboration is anchored more in community embeddedness and shared responsibility for market development, rather than in business growth and success replication. While the craft scene acknowledges the inspirational success of 'one of their own', strategic drive comes from more localised relations and a desire for independence. This has implications not only for craft beer but also on how collaboration among entrepreneurs sustains in respond to success from within the group.